2017
DOI: 10.1002/jsfa.8601
|View full text |Cite
|
Sign up to set email alerts
|

Sequential extraction of flavonoids and pectin from yellow passion fruit rind using pressurized solvent or ultrasound

Abstract: With this study it can be concluded that mixtures of alcohols with water favor the extraction of bioactive compounds of passion fruit peel. Both PSE and UAE were effective in sequentially extracting flavonoids and pectin. The preferred solvent is ethanol due to its lower toxicity. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Tropical fruits have been also studied in the last years to obtain HMP. For example, passion fruit rind [54,62], durian rind [46] or jackfruit peels [51,52,63] have been proposed as interesting sources of pectins. Hydrothermal extraction is also the most used method in these types of wastes.…”
Section: Sources Of Pectinmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropical fruits have been also studied in the last years to obtain HMP. For example, passion fruit rind [54,62], durian rind [46] or jackfruit peels [51,52,63] have been proposed as interesting sources of pectins. Hydrothermal extraction is also the most used method in these types of wastes.…”
Section: Sources Of Pectinmentioning
confidence: 99%
“…Results showed that the obtained pectin was mainly formed by homogalacturonans. Furthermore, their high degree of methylation indicated that the passion fruit pectin could be applied in gel forming products [62].…”
Section: Sources Of Pectinmentioning
confidence: 99%
“…It is a widely used functional food raw material with high value in reducing cholesterol levels, reducing hyperlipidemia, and hypertension, improving glucose tolerance and insulin response, helpful to gastrointestinal health and the prevention of some cancers. Pectin is used as a nutritional fiber delivery, gelling agent, and edible coating and stabilizer in the pharmaceutical, cosmetic and food industry, especially in the production of confectionery, jelly, and other products (de Souza et al, 2018). Pectin-based edible coating plays a waterproof role in fruit preservation, which have the functions of preventing moisture transfer and flavor loss, and improving hardness.…”
Section: Processing and Applicationsmentioning
confidence: 99%
“…In the literature, studies that evaluated the efficiency of flavonoid extraction methods in passion fruit can be observed [ 8 , 14 , 24 , 25 ], but there is scarcity in mentioning and/or applying Green Analytical Chemistry concepts within this context. Flavonoid extraction based on Green Analytical Chemistry intends to look for alternative and non-toxic solvents, increased energy efficiency and greater extraction yield, as well as reduced operation time, at a lower cost and aiming to mitigate the environmental impacts.…”
Section: Introductionmentioning
confidence: 99%